Introduction to the special issue on computational logic for verification. Issue 2 (11th May 2018) - VIDAL, GERMÁN
Abstract : Logic underlies many fundamental techniques in computer science. It helps us to rigorously formalize these techniques and prove them correct. The last decade has witnessed a growing interest in the use of computational logic methods for program verification. It has attracted researchers from both computational logic and program verification communities, giving rise to a fruitful exchange of ideas and experiences.